ANALISIS KESTABILAN PENYELENGGARAAN PROSES PEMBELAJARAN PADA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS HASANUDDIN PERIODE 2017/2018 - Sumardi Lasise (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2019)
This study aims to determine, explain and analyze the stability of the implementation of the learning process at the Faculty of Economics and Business, University of Hasanuddin (FEB-UH). The sample of all 145 alumni graduating in an odd semester of 145 people and an even semester of 155 people by photocopying the archives in the academic administration section of the Faculty of Economics and Business, especially in the Undergraduate Program (S1). The results showed that the implementation of the learning process has a fairly good level of stability, although there are wide variations according to the regulations applied at Hasanuddin University. The variation on the duration of the study completion means that the time and money that must be incurred to complete the study also varied; the longer the duration of student study completion, the more the time and money must be spent by students and vice versa.